Canada and the OAS: the Vacant Chair Revisited - Pharand, Donat (Revue générale de droit, 1986)
Two basic questions are examined: first, why has the CANADA chair in the Council's room of the OAS remained unoccupied since 1910, and, second, should Canada occupy that chair. The answer to the first question lies in Canada's perception of itself as a north Atlantic country, belonging more to Europe than to the Americas. On the second question, the author's opinion is that Canada should take its seat in the OAS, in order to better promote stability in the hemisphere through peaceful solutions of the economic and social problems, which are at the basis of the unrest in the region.